Pengaruh Kepemimpinan Transformasional Terhadap Kepuasan Kerja - Izma Azhari; Ma'mun Sutisna (Jurnal Riset Bisnis dan Investasi, 2016)
Transformational leadership is one of the important things that must be considered by a company because it has a positive impact on increasing employees job satisfaction. Satisfied employees will have a willingness to do more than expected so that the goals can be achieved. This must be applied to PT LEN Industri (Persero), a SOEs that is engaged in industrial electronics. This research aims to know the description of transformational leadership, job satisfaction, and the influence of transformational leadership on job satisfaction in PT LEN Industri (Persero). The research method used a quantitative research with technical data analysis includes classic assumption test, descriptive statistics, analysis of relationships, and analysis of influence. Respondents in this research used 172 employees originating from 14 departments in PT LEN Industri (Persero) with proportionate stratified random sampling methods. Transformational leadership variable used an instrument from Multifactor Leadership Questionnaire (MLQ) and job satisfaction variable used an instrument from Job Satisfaction Survey (JSS). The results obtained transformational leadership in the medium category, the job satisfaction in the high category, and the transformational leadership contributed amounted to 56.8% against the influence of job satisfaction in PT LEN Industri (Persero). Management is expected to increase the transformational leadership factors, so job satisfaction will increase too.